2014
DOI: 10.1145/2661229.2661275
|View full text |Cite
|
Sign up to set email alerts
|

Hierarchical diffusion curves for accurate automatic image vectorization

Abstract: Figure 1:We are able to accurately vectorize raster images ("Input") by automatically tracing a sparse set of multi-scale diffusion curves to a broad class of images, including vector art (i.e., diffusion curve images), fluid simulations with turbulent flows, and natural images. AbstractDiffusion curve primitives are a compact and powerful representation for vector images. While several vector image authoring tools leverage these representations, automatically and accurately vectorizing arbitrary raster image… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
50
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 45 publications
(55 citation statements)
references
References 27 publications
1
50
0
Order By: Relevance
“…Solid color and gradient fills later became standard and permitted the compact representation of a wide range of expressive, scalable images. More recently, research has sought to increase the expressive range of colors and textures in vector graphics via methods that can be classified as patch-based [13,31], mesh-based [12,29], and curve-based [32].…”
Section: Related Workmentioning
confidence: 99%
See 2 more Smart Citations
“…Solid color and gradient fills later became standard and permitted the compact representation of a wide range of expressive, scalable images. More recently, research has sought to increase the expressive range of colors and textures in vector graphics via methods that can be classified as patch-based [13,31], mesh-based [12,29], and curve-based [32].…”
Section: Related Workmentioning
confidence: 99%
“…Several other papers use a bi-Laplacian formulation of diffusion curves in order to provide more control over color diffusion from boundary curves [2,4,8]. Xie et al [32] proposed an automatic vectorization method based on extracting hierarchical diffusion curves in both the Laplacian and bi-Laplacian domains. Although their work achieves a high-quality reconstruction both for vector art and for natural images, their diffusion curves and colors are mostly static and cannot be edited later, apart from tasks such as detail removal and stylization.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…This behaviour is conceptually similar to Hermite curve interpolation as sketched at the top of Figure 2, and it is clearly not desirable in 2D image editing and animation applications. Recently, Xie et al [XSTN14] showed how to automatically convert a raster image to a set of Bezier curves together with a Bilaplace image model. Another issue is that Bilaplace functions are known to be much more computationally expensive and subject to numerical instability because the system is less well-conditioned, as opposed to Laplace functions.…”
Section: Introductionmentioning
confidence: 99%
“…But this makes fitting a given color image to a set of Bezier curves challenging because selecting the right constraints is not trivial. Recently, Xie et al [XSTN14] showed how to automatically convert a raster image to a set of Bezier curves together with a Bilaplace image model. However, their representation is based on the boundary element method so that colors and Bezier curve geometry remain mostly static, i.e., both cannot be edited later.…”
Section: Introductionmentioning
confidence: 99%